Motivation and Islamic Leadership in Global Era - Rajab, Effendy (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary Sciences, 2020)
Job design can affect the outcomes that the individual values. Our volunteers, having worked in various organizations inevitably discover through their experience in different jobs what kinds of outcomes to expect. Changes in the work environments do and can affect the perception of what is available, thus shaping the outcomes valued. By and large, the motivation of individuals, can be strengthened if the job or the task assigned is designed to meet the higher order needs of individuals, such as the need for recognition, for esteem and for self-actualization.